Patterns of recurrence after selective postoperative radiation therapy for patients with head and neck squamous cell carcinoma. Issue 1 (December 2016) - Murakami, Naoya; Matsumoto, Fumihiko; Yoshimoto, Seiichi; Ito, Yoshinori; Mori, Taisuke; Ueno, Takao; Tuchida, Keisuke; Kashihara, Tairo; Kobayashi, Kazuma; Harada, Ken; Kitaguchi, Mayuka; Sekii, Shuhei; et al.
Abstract Background The radiation field for patients with postoperative head and neck squamous cell carcinoma is narrower in our institution than in Western countries to reduce late radiation related toxicities. This strategy is at a risk of loco-regional or distant metastasis. However, because patients are more closely checked than in Western countries by every 1 to 2 months intervals and it is supposed that regional recurrences are identified and salvage surgeries are performed more quickly. Therefore, it is considered that patient survival would not be compromised with this strategy. The aim of this study was to investigate the feasibility of this strategy retrospectively. Methods Patients who underwent neck dissection with close or positive margin, extra-capsular spread (ECS), multiple regional lymph node metastasis, pT4, with or without primary tumor resection were treated with postoperative radiation therapy. The volume of radiation field, especially the coverage of prophylactic regional lymph node area, was discussed among head and neck surgeons and radiation oncologists taking into account the clinical factors including patient's age, performance status, number of positive lymph nodes, size of metastatic lymph nodes, extension of primary tumor beyond the midline, and existence of ECS. Results Seventy-two patients were identified who were treated with postoperative radiation therapy for head and neck squamous cell carcinoma between November 2005 and December 2014. There were 20 patients with oropharynx, 19 with hypopharynx, 7 with larynx, 23 with oral cavity, and 3 with other sites. Thirty eight patients had their neck irradiated bilaterally and 34 unilaterally. Median follow-up period for patients without relapse was 20.7 months (5.1–100.7). Thirty two patients had disease relapse after treatment including 22 loco-regional recurrence and 14 distant metastases. Among 22 loco-regional recurrence, seven patients underwent salvage surgery and one of them was no relapse at the time of the analysis. Among patients without bilateral neck lymph node metastasis who were treated with unilateral neck irradiation, patients with oral cavity or recurrent disease had significantly lower DFS compared with those without (2-y DFS 41.7 % vs 88.2 %, p  = 0.017). Conclusions In patients without bilateral neck lymph node involvement, the postoperative unilateral neck irradiation is a reasonable treatment strategy for patients with the exception of oral cavity or recurrent disease.